Food allergy: cause or consequence of pediatric eosinophilic esophagitis? Potential implications of ultraprocessed foods in prevention and management - Carucci, Laura; Votto, Martina; Licari, Amelia; Marseglia, Gian Luigi; Berni Canani, Roberto (Frontiers in Allergy, 2023)
Eosinophilic esophagitis (EoE) is a chronic, immune-mediated disease characterized by eosinophilic infiltration, leading to esophageal dysfunction, inflammation, and fibrotic remodeling. In the last few decades, there has been an increased prevalence of EoE at an alarming rate in the pediatric age. The pathogenesis of EoE is still largely undefined, and this limits the definition of effective strategies for the prevention and management of this condition. EoE is considered a multifactorial disease arising from a negative interaction between environmental factors and genetic background, causing an impaired esophageal epithelial barrier with subsequent abnormal allergen exposure activating type 2 (Th2) inflammation. Food antigens have been suggested as key players in Th2 inflammation in pediatric patients with EoE, but emerging evidence suggests a potential role of other dietary factors, including ultraprocessed foods, as possible triggers for the occurrence of EoE. In this paper, we discuss the potential role of these dietary factors in the development of the disease, and we propose a new approach for the management of pediatric patients with EoE.